A Retrospective Claims-Based Study Evaluating Clinical and Economic Burden Among Patients With Moderate to Severe Osteoarthritis Pain in the United States - Patricia B. Schepman; Sheena Thakkar; Rebecca L. Robinson; Craig G. Beck; Deepa Malhotra; Birol Emir; Ryan N. Hansen (Journal of Health Economics and Outcomes Research)
**Background:** There has been limited evaluation of medication adherence, healthcare resource utilization (HCRU), and healthcare costs over time in patients with osteoarthritis (OA), and stratification by pain severity level has not been reported. Assessing such longitudinal changes may be useful to patients and healthcare providers for tracking disease progression, informing treatment options, and employing strategies to optimize patient outcomes. **Objectives:** To characterize treatment patterns, HCRU, and costs over time in patients with moderate to severe (MTS) OA pain in the United States. **Methods:** We conducted a retrospective claims analysis, using IBM® MarketScan® databases, from 2013-2018. Eligible patients were aged ≥45 years with ≥12 months pre-index (baseline) and ≥24 months (follow-up) of continuous enrollment; index date was defined as a physician diagnosis of hip or knee OA. An algorithm was employed to identify MTS OA pain patients, who were propensity score matched with patients having non-MTS OA pain. Data were summarized using descriptive statistics and univariate analyses. **Results:** After propensity score matching, the overall OA pain cohorts consisted of 186 374 patients each: 61% were female, mean age was 63 years, and two-thirds (65.6%) were of working age (45-65 years). Sleep-related conditions, anxiety, and depression were significantly higher in the MTS OA pain cohort vs non-MTS (_P_<0.001). At baseline and 12- and 24-month follow-ups, receipt of prescription pain medications, HCRU, and direct medical costs were significantly higher in the MTS OA pain cohort (all _P_<0.01). Medication adherence was significantly higher in the MTS OA pain cohort for all medication classes except analgesics/antipyretics, which were significantly lower vs the non-MTS OA pain cohort (all _P_<0.0001). **Conclusions:** The burden of MTS OA pain is substantial, with patterns that show increasing medication use, HCRU, and costs vs non-MTS OA pain patients over time. Understanding the heterogeneity within the OA population may allow us to further appreciate the true burden of illness for patients in pain.